An Integrative Model Accounting for the Symptom Cluster Triggered After an Acoustic Shock. (September 2018) - Noreña, Arnaud J.; Fournier, Philippe; Londero, Alain; Ponsot, Damien; Charpentier, Nicolas
Acoustic shocks and traumas sometimes result in a cluster of debilitating symptoms, including tinnitus, hyperacusis, ear fullness and tension, dizziness, and pain in and outside the ear. The mechanisms underlying this large variety of symptoms remain elusive. In this article, we elaborate on the hypothesis that the tensor tympani muscle (TTM), the trigeminal nerve (TGN), and the trigeminal cervical complex (TCC) play a central role in generating these symptoms. We argue that TTM overuse (due to the acoustic shock), TTM overload (due to muscle tension), and ultimately, TTM injury (due to hypoxia and "energy crisis") lead to inflammation, thereby activating the TGN, TCC, and cortex. The TCC is a crossroad structure integrating sensory inputs coming from the head–neck complex (including the middle ear) and projecting back to it. The multimodal integration of the TCC may then account for referred pain outside the ear when the middle ear is inflamed and activates the TGN. We believe that our model proposes a synthetic and explanatory framework to explain the phenomena occurring postacoustic shock and potentially also after other nonauditory causes. Indeed, due to the bidirectional properties of the TCC, musculoskeletal disorders in the region of the head–neck complex, including neck injury due to whiplash or temporomandibular disorders, may impact the middle ear, thereby leading to otic symptoms. This previously unavailable model type is experimentally testable and must be taken as a starting point for identifying the mechanisms responsible for this particular subtype of tinnitus and its associated symptoms.